Impact of earnings quality on company's performance: a literature review - Duarte, Ana Filipa (2021)
Purpose: Stakeholders use financial information in their decision-making process. Although, if financial information lacks appropriate quality, stakeholders’ perceptions will be biased. Thus, understanding earnings quality is crucial. Earnings quality is linked with the thematic of earnings management, as managing earnings is likely to decrease their quality. More recently, the literature has turned its attention to the impact of earnings quality on company’s performance. This work aims to understand the characteristics of earnings quality and how can it be measured. Additionally, it plans to investigate the impact of earnings quality on company’s performance. Methodology: This work is a literature review about earnings quality and its impact on company’s performance. Seven characteristics of earnings quality are simultaneously considered: accruals quality, persistence, predictability, smoothness, value relevance, timeliness, and conservatism. Different measures of these characteristics are analyzed, by explaining the differences among them and identifying the specific cases when these characteristics can be used. Moreover, the impact of earnings quality on company’s performance is analyzed to investigate if low earnings quality has a negative impact on company’s performance. Different measures of performance/ratios are also addressed, both market-based and accounting-based. Findings: High earnings quality usually has a positive impact on performance since the investment and financing decisions are based on correct information, thus increasing company’s profits and value creation. The use of earnings management practices, or of other techniques that reduce earnings quality, increase the probability of financial distress, as decisions may not be accurate, and the company’s financial situation may be different from the one presented in the financial statements. Originality: This paper presents an in-depth study of earnings quality and its impact on company’s performance. Most studies focus on earnings management, or other specific characteristic of earnings quality, but in an isolated perspective. Few studies consider the seven characteristics of earnings quality simultaneously. This study addresses this caveat. Moreover, the impact of earnings quality on performance is also relevant, especially to stakeholders, for a better understanding of the company’s financial information and for better decision making that can increase the company’s value.